P209 THE FOLLOW–UP OF PATIENTS AFTER ACUTE CORONARY SYNDROME: THE APULIAN PONTE–ACS PROJECT. (18th May 2022) - Scicchitano, P; Locuratolo, N; Lillo, A; Sublimi Saponetti, L; Palumbo, V; Lanzone, S; Campanella, C; Mancini, L; Massari, F; Landriscina, R; Barba, G; De Santis, A; et al.
Abstract: Background: Patients discharged after acute coronary syndrome (ACS) deserve a tight follow–up in order to optimize long–term pharmacological treatments and prevent the occurrence of adverse events. The aim of the PONTE–ACS Project was to evaluate the impact of a dedicated cooperative program between hospital and outpatient structures on the persistance on recommended therapies and long–term outcome occurrence in patients discharged after ACS. Materials and Methods: This was a prospective, longitudina, cohort study. We enrolled patients who were discharged after ACS and/or after coronary revascularization in the HUB centres of ASL Bari. Patients underwent cardiologic evaluation and laboratory examination at 30 days, 3–, 6–, and 12–months from the index event. The following endpoint were considered: all–cause mortality, ACS recurrence/cardiac ischemia/angina, restenosis/intrastent thrombosis, stroke/transient ischemic attack (TIA), heart failure, any bleeding. Adherence and persistence to therapies were evalauted as well as the percentage of patients who reached the recommended goals. Results: We enrolled 2476 patients (77.4% male, mean age: 67.2±12.0 yrs). After one–year follow–up, 99.5% (p < 0.05) were on statin–therapy, 16.1% with ezetimibe (p < 0.01) and 9.9% (p < 0.01) with proprotein convertase subtilisin/kexin type 9 inhibitors. The overall mortality at one–year follow–up was 3.1%, while ACS recurrence/cardiac ischemia/angina and restenosis/intrastent thrombosis were 3% e 1.3%, respectively. Any bleeding rate was 2.2%. Conclusions: The PONTE–ACS Project was able to improve the management of patients after ACS, to manage a structured follow–up protocol for patients discharged after ACS and/or coronary revascularization, thus improving adhesion to recommended therapies and keeping lower the incidence of major cardiovascular and bleeding events.